Characterisation of phenolics, betanins and antioxidant activities in seeds of three Chenopodium quinoa Willd. genotypes. (1st January 2015) - Tang, Yao; Li, Xihong; Zhang, Bing; Chen, Peter X.; Liu, Ronghua; Tsao, Rong
Highlights: Difference in phenolic content and composition of quinoa seeds of different colour. Identification of free and conjugated phenolics by LC–ESI-MS. First report of the identification of betacyanins in red and black quinoa. Phenolic compounds contribute significantly to the antioxidant activities. Darker quinoa seeds had higher levels of phenolics and antioxidant activities. Abstract: Quinoa ( Chenopodium quinoa Willd.) is known for its exceptional nutritional value and potential health benefits. The present study identified the composition of different forms of extractable phenolics and betacyanins of quinoa cultivars in white, red and black, and how they contribute to antioxidant activities. Results showed that at least 23 phenolic compounds were found in either free or conjugated forms (liberated by alkaline and/or acid hydrolysis); the majority of which were phenolic acids, mainly vanillic acid, ferulic acid and their derivatives as well as main flavonoids quercetin, kaempferol and their glycosides. Betacyanins, mainly betanin and isobetanin, were confirmed for the first time to be the pigments of the red and black quinoa seeds, instead of anthocyanins. Darker quinoa seeds had higher phenolic concentration and antioxidant activity. Findings of these phenolics, along with betacyanins in this study add new knowledge to the functional components of quinoa seeds of different cultivar background.